An Automatic Generation Method of Train Network Equipment Code Based on Configurable Hardware - XIONG Yan; ZHANG Bao; YANG Feng; HUANG He; LIN Lei (Kongzhi Yu Xinxi Jishu)
With wide application of the box network products with configurable hardware in the train, the difference of box configuration results in a large amount of manpower investment in the development of application software, and the quality of software cannot be guaranteed. For this reason, this paper proposed a method of automatic code generation, and designed a set of automatic code generation tools based on this method to realize the automatic code generation. Experimental results show that the tool can save more than 90% of the development time and reduce the software error rate to 0.